Trade openness and economic growth nexus: Exploring the role of institutional quality in Nigeria - Philip Chimobi Omoke; Silva Opuala-Charles (Cogent Economics & Finance, 2021)
This study attempts to fill the prior knowledge gap in the nexus between trade openness and economic growth in Nigeria by incorporating the role of institutional quality. The study covers the period from 1984 to 2017 and employs three indicators of trade openness including total trade, import trade, and export trade. Cointegration among the variables is examined using the ARDL bounds testing approach. The results provide evidence of a long-run relationship among the variables. The estimates suggest that export trade has a significant positive impact on economic growth while the impact of import trade on economic growth is negative and significant. The results also show that the negative long-run effects of import trade on economic growth in Nigeria decreases as institutional quality (quality of governance) improves. These empirical results have important policy implications for Nigeria. Among others, this study highlights the needs to improve the quality of governance in the country. Good governance and quality institutions can help channel the dividends of trade openness into growth-enhancing activities.
Keywords: 330; Economic growth; institutional quality; Nigeria; Trade openness